Design real-time reversal of tumor multidrug resistance cleverly with shortened carbon nanotubes - Wu P; Li S; Zhang H (Dove Medical Press, 2014)
Pingping Wu,1 Shang Li,2 Haijun Zhang2 1Jiangsu Cancer Hospital, Nanjing, People’s Republic of China; 2Department of Oncology, Zhongda Hospital, Medical School, Southeast University, Nanjing, People’s Republic of ChinaAbstract: Multidrug resistance (MDR) in tumors renders many currently available chemotherapeutic drugs ineffective. Research in nanobiotechnology-based therapeutic alternatives has provided innovative and promising strategies to overcome MDR. The aim of this study was to investigate whether the new strategy of a co-loaded reversal agent and chemotherapeutic drug with shortened carbon nanotubes (CNTs) would show useful effects on the real-time reversal of tumor MDR. CNTs were cut and purified via ultrasonication and oxidative acid treatment to optimize their length for drug-delivery vehicles, then verapamil (Ver) and doxorubicin (Dox) were co-loaded on shortened CNTs (denoted as Ver/Dox/shortened CNTs), which acted as a drug delivery system. The multidrug resistant leukemia K562/A02 cells were treated with the denoted Ver/Dox/shortened CNTs. The real-time reversal of tumor MDR were evaluated by flow cytometer, 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assays, acridine orange/ethidium bromide staining, and Western blot analysis. In the same MDR tumor cells the new strategy of a co-loaded reversal agent and chemotherapeutic drug with CNTs could inhibit the function of P-glycoprotein in real-time by Ver as reversal agent, significantly increase the uptake of Dox, enhance the sensitivity of the MDR cancer cells to the chemotherapeutic agent, and induce apoptosis. It was therefore concluded that a co-loaded reversal agent and chemotherapeutic drug with shortened CNTs could have real-time reversal ability of MDR in tumors, which could represent a promising approach in cancer therapy.Keywords: multidrug resistance, carbon nanotubes, drug delivery system, tumor